Determinants of Purchase Intention On TikTok As An E-WOM Platform - Siti Mariam; Rizka Diah Agustia; Abdul Haeba Ramli (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Social media platforms have revolutionized how consumers receive and evaluate product information, particularly through Electronic Word of Mouth (E-WOM). TikTok, with its interactive features and large user base, has emerged as a powerful E-WOM medium that can influence consumer behavior. This study investigates the impact of E-WOM components—information quality, credibility, suitability, and needs—on information usefulness, information adoption, and ultimately purchase intention for Wardah cosmetic products. A quantitative, descriptive-causal research design was applied using purposive sampling, with 160 respondents from the JABODETABEK area who had purchased Wardah products at least twice in 2023. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that all proposed relationships are statistically significant: E-WOM attributes positively affect information usefulness, which in turn influences information adoption and purchase intention. This study contributes to a deeper understanding of the role of E-WOM in digital consumer behavior and offers practical insights for cosmetic brands aiming to leverage social media platforms for marketing strategies. Keywords: E-WOM, information usefulness, information adoption, purchase intention, TikTok, Wardah cosmetics